Polimorfismos em 11 genes de antígeno leucocitário humano em pacientes hospitalizados por covid-19 : estudo multicêntrico em cinco regiões do Brasil - Berber, Gilcele de Campos Martin (2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), emerged at the end of 2019 and has evolved into a global pandemic, with 766 million confirmed cases and 6.9 million deaths worldwide. Studies have shown that the spectrum of clinical evolution may involve immunogenetic factors. Therefore, chapter 2 review pathogenesis aspects, the immune response against the virus and the influence of immunogenetic factors in COVID-19 patients with genetic characteristics distinct from Brazilian population. With the aim of understanding the association of these factors in the Brazilian population, 834 Brazilian patients diagnosed by RT-qPCR positive for SARS-CoV-2 from Ceará (n=110), Pará (n=209), Mato Grosso (n=192), Rio de Janeiro (n=211) and Rio Grande do Sul (n=112), presenting different manifestations and clinical outcomes, were allocated into hospitalized (moderate to critical; n=487) and non-hospitalized (mild or asymptomatic; n=347) groups. Patients were genotyped for 13,000 single nucleotide polymorphisms (SNPs) in human leucocyte antigen (HLA I and II) genes, using AxiomTM Human Genotyping SARS-COV-2 and analyzed by bioinformatic imputation in chapter 3. Epidemiological data (age, sex, clinical and evolutionary signs, comorbidities) were compared using mixed regression models controlling for covariates. Of the 26 candidate HLA alleles identified, in a primary analysis, only DQA1*05:01 (p=0.015) in the state of Ceará and DQA1*04:01 (p=0.0363) in the state of Pará remained with a significant p-value after multiple tests correction. For the meta-analysis, the comparison between hospitalized (H) and nonhospitalized (NH) groups revealed the association of HLA-A*30:02 (p=0.0247) and HLAC*03:04 (p=0.0205) alleles with an increased risk for hospitalization, whereas the HLAC*01:02 (p=0.0181) allele showed a protective effect against hospitalization. For HLA class II alleles, five showed a significant difference in frequencies between the study groups; the DPA1*02:01 (p=0.0259), DQA1*05:01 (p=0.0133) and DRB1*03:01 (p=0.0276) alleles associated with increased risk for hospitalization and, a protective effect was observed for DPA1*01:03 (p=0.0229) and DPB1*04:01 (p=0.0474) alleles. HLA evolutionary divergence (HED) scores were significantly higher only for HLA-A loci in the non-hospitalized group. Furthermore, the male gender, advanced age and the presence of comorbidities related to worse prognosis and a greater necessity for hospital support in the study population. These findings support the idea that specific HLA alleles may act as protective or predisposing factors, associated with the risk of hospitalization for COVID-19. There is a direct relationship between the diversity of alleles and more effective immune response, protecting against severe forms of COVID- 19.